PKM Training on Techniques for Making Ecoenzyme Derivative Products for Community Groups in the Santa Brigida Region, Raja Damai Church, Tikala Baru District, Manado - Tumbelaka, Selvie; Wantasen, Sofia; Ogie, Tommy B.; Lumingkewas, Adeleyda M.W. (Journal of Literacy and Education, 2025)
Waste is still a serious problem that cannot be completely addressed, especially in big cities. The increase in the amount of waste will continue to increase in line with the increase in people's welfare and lifestyle. Ecoenzymes are useful multipurpose liquids that can be made from organic waste resulting from household activities. Community involvement in waste management is still lacking due to the lack of training on processing organic waste into ecoenzymes, and processing ecoenzymes into derivative products in the form of soap. The method used in this PKM is training and mentoring which consists of two stages, namely the practice of making ecoenzymes and the next stage the practice of making soap from ecoenzymes. The results of the evaluation carried out after training by the PKM Team showed that the partner group members were able to absorb the knowledge and information provided so that they were able to make ecoenzymes from organic materials which are household waste, and then the ecoenzymes that had been harvested (after 3 months of fermentation) could be processed into soap products. solid that can be used for family needs. This shows that the PKM activity of training on techniques for making ecoenzyme derived products has succeeded in increasing the knowledge and skills of partner groups in making ecoenzymes and soap derivative products, which are also an alternative for handling organic waste in the environment.